Customized Digital Restoration: An Innovative Minimally Invasive Approach to Restore Young Permanent Molars: Case Series - Gaurav Gupta; Dinesh Kumar Gupta; Priyanka Gupta; Parth Shah (Journal of South Asian Association of Pediatric Dentistry)
Background: Crowns are provided for teeth that have extensive caries, developmental defects, or decalcified following pulpectomy/root canal treatment (RCT). Until now, prefabricated crowns have been available of varying sizes to match molars which require replacement after adolescence. Materials and methods: This case series illustrates an innovative technique of customized digital restoration (CDR) with the use of computer-aided design and manufacturing (CAD-CAM) for the fabrication of customized tooth-colored zirconium restoration for grossly decayed young permanent molars. Result: Customized digital restoration is made through CAD-CAM which is more precise for young permanent molars. Conclusion: This approach has the advantage of customization and definitive restoration in contrast to the prefabricated, unesthetic, and provisional options.